Research on the Development Strategy of Buddhist Cultural Tourism Resources in Inner Mongolia: Taking Guanyin Temple in Baotou City as an Example - Yan, Han (International Journal of Global Economics and Management, 2024)
Religious culture, as an excellent tourism resource, not only attracts tourists but also deepens the spiritual connotation of scenic spots. Starting from the current situation of the development of Buddhist tourism resources in Inner Mongolia, this article takes Guanyin Temple in Baotou City as an example to analyze the many problems that exist in the current development of Buddhist tourism resources in Inner Mongolia. In response to these problems, strategies for developing and utilizing Buddhist tourism resources are discussed. Combining the unique regional culture of Guanyin Temple, create a unique religious and cultural tourist destination. Its planning strategy hopes to provide reference for the development of religious and cultural tourism in Guanyin Temple.